2014
DOI: 10.1016/j.bbrc.2014.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulatory action of olfactory ensheathing glia-conditioned medium on oligodendroglial differentiation, with additional reference to signaling mechanisms

Abstract: We examined the effects of conditioned medium from olfactory ensheathing glia (OEGCM) on the differentiation of oligodendrocytes in mixed cultures of early postnatal hippocampi. Differentiation was judged from the numerical density (ND) of cells immunoreactive to 2'3' cyclic nucleotide 3'phosphodiesterase (CNPase) and O4 antibodies. NDs increased according to inverted-U dose-response curves, particularly for CNPase+ cells (9-fold at optimal dilution) and these changes were blocked by inhibitors of ERK1, p38-MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…as modified by our group720. Eight-week-old male Wistar rats were obtained from the Center for Experimental Surgery Laboratory at the Federal University of Rio de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
“…as modified by our group720. Eight-week-old male Wistar rats were obtained from the Center for Experimental Surgery Laboratory at the Federal University of Rio de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
“…OEGs primary cell cultures were harvested from the olfactory bulb (OB) of adult Wistar rats (3-4 months) as previously reported (Carvalho et al, 2014), and at least 20 animals were used in this study. The OEG primary cell culture was also performed following a protocol previously described (Nash et al, 2001;Carvalho et al, 2014). Briefly, the olfactory fiber layer from the OB was dissociated and purified by differential adhesion (Nash et al, 2001), and then cells were placed on coverslips, T25 plates and/or 6-well plates previously treated with laminin (40 µg/ml, Sigma Aldrich) in complete DMEM-F12 supplemented with 10% fetal bovine serum and incubated in 5% CO 2 at 37 • C. After the OEG cell culture reached 80% confluence, the OEGCM was collected, filtered (0.22 µm membrane pore), aliquoted and stored at −70 • C until use.…”
Section: Primary Cell Cultures From Oeg and Oegcmmentioning
confidence: 99%
“…We first isolated and cultured olfactory ensheathing glia (OEG) from the olfactory bulbs of adult rats following a protocol previously established by us and others (Nash et al, 2001;Carvalho et al, 2014Carvalho et al, , 2018. We also investigated if OEG in culture expresses components of the ECS, i.e., cannabinoid receptor type 1 (CB1), and the main endocannabinoid degradation enzymes, fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), which degrade anandamide (AEA) and 2-arachidonoyl glycerol (2-AG), respectively, by qRT-PCR (Figure 1A).…”
Section: Highly Purified Oegs Culture Expresses Markers Of the Endoca...mentioning
confidence: 99%
“…Olfactory ensheathing cells were purified from the olfactory bulbs of C57BL/6 male adult mice following our and others' previously described protocol (11)(12)(13)(14)(15). Briefly, the mice were killed by isoflurane.…”
Section: Cell Culture Of Olfactory Ensheathing Cellsmentioning
confidence: 99%
“…We purified the olfactory ensheathing cells from the olfactory bulbs of C57BL/6 male adult mice following previously established protocol (11)(12)(13)(14)(15) (summarized in Figure 1A). Costaining of OECs for 2 0 ,3 0 cyclic nucleotide 3 0 -phosphodiesterase, smooth muscle a-actin, glial fibrillary acidic protein, and calciumbinding protein b, specific markers for OEC (13), revealed that our cultures displayed neither unlabeled cells nor cells labeled with only one marker, confirming that our method is highly effective for OEC purification (Figure 1B).…”
Section: Isolation and Characterization Of Oec Culturesmentioning
confidence: 99%